The role of macrophage migratory behavior in development, homeostasis and tumor invasion - Murrey, Michael W.; Ng, Isaac Trinstern; Pixley, Fiona J. (Frontiers in Immunology, 2024)
Tumor-associated macrophages (TAMs) recapitulate the developmental and homeostatic behaviors of tissue resident macrophages (TRMs) to promote tumor growth, invasion and metastasis. TRMs arise in the embryo and colonize developing tissues, initially to guide tissue morphogenesis and then to form complex networks in adult tissues to constantly search for threats to homeostasis. The macrophage growth factor, colony-stimulating factor-1 (CSF-1), which is essential for TRM survival and differentiation, is also responsible for the development of the unique motility machinery of mature macrophages that underpins their ramified morphologies, migratory capacity and ability to degrade matrix. Two CSF-1-activated kinases, hematopoietic cell kinase and the p110δ catalytic isoform of phosphatidylinositol 3-kinase, regulate this machinery and selective inhibitors of these proteins completely block macrophage invasion. Considering tumors co-opt the invasive capacity of TAMs to promote their own invasion, these proteins are attractive targets for drug development to inhibit tumor progression to invasion and metastasis.